Peritoneal simple mesothelial cyst: a case report - Yu. V. Popov; N. S. Vanke; A. G. Kedrova (ABV-press, 2019)
Primary retroperitoneal cysts are rare benign growths that are often random findings during diagnostic examinations or surgical treatment. The classification, etiology and clinical manifestations of retroperitoneal cysts are the subject of interdisciplinary debate. The most reliable test for their detection is ultrasound and computed tomography. Based on the available literature data, primary cysts of the retroperitoneal space are subject to complete removal within healthy tissues.We present a clinical case of intraoperative detection of a large-sized retroperitoneal cyst in a 42-year-old woman hospitalized in the gynecological department of the Federal Research and Clinical Center for Specialized Medical Care and Medical Technologies, Federal Medical and Biological Agency of the Russian Federation, for surgical treatment of uterine myoma. During the planned surgical treatment revealed the presence of cystic formation of large sizes in the right anterior pararenal space. The final diagnosis was made after a pathological examination. Histologically, the inner epithelial lining of the cystic formation contained multiple ciliary cells, forming papillary structures similar in some areas, with folds of the mucous membrane of the fallopian tube.